MAKING PLACES FOR PEOPLE 12 questions every designer should ask. - Coffin, Christie; Young, Jenny (Jenny E.) ([S.l.] : ROUTLEDGE, 2024)
Making Places for People explores 12 social questions crucial to environmental design. Authors Christie Johnson Coffin and Jenny Young bring perspectives from practice and teaching to challenge assumptions about how places meet human needs. In this expanded second edition, the authors continue to explore the complexities of basic questions, such as: What is the story of this place? What logic orders it? How big is it? How sustainable is it? They consider the impact on making places of pandemic, climate change, human migration, and contemporary discussions of diversity, equity, and justice. Short, approachable, easy-to-read chapters, illustrated with updated examples of projects from around the world, bring together theory, methodology and key research findings. Understanding experienced and research-based connections between people and built form can inspire designs that make places of meaning and delight. This second edition will be essential reading for design students and professionals.
Keywords: Architecture -- Human factors; Architecture and society; Architectural design; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Landscape; ARCHITECTURE / Interior Design / General